Refugee Stigma and Its Association with Depression Symptom Severity: Findings from Urban Refugees Living in Mbarara City, Southwestern Uganda - Bahati, Ronald; Ainamani, Herbert Elvis; Ashaba, Scholastic; Sigmund, Cathy Denise; Rukundo, Godfrey Zari (Open Journal of Psychiatry, 2022)
Introduction: Refugees in urban areas often face acculturation challenges, stigma, and stereotypes that impact their mental well-being. The aim of the present study was to examine the prevalence of stigma and its association with depressive symptoms among urban refugees living in Mbarara city, southwestern Uganda. Methods: This cross-sectional study used snowball sampling and interviewed 343 refugees residing in Mbarara city, southwestern Uganda. The Discrimination and Stigma Scale was used to assess stigma, whereas the Patient Health Questionnaire (PHQ-9) was used to screen for depression symptoms severity. Linear regression models determined the associations between stigma and depression symptoms severity. Data were collected between June 2019 and March 2020. Findings: Of the 343 participants, 198 were males and 145 were females; their mean age was 28.8 years (SD = 11.0). Most of the participants (95.3%) had attained formal education. Our findings show that 84% (n = 288) of the participants had symptoms of stigma. Stigma had a statistically significant positive association with depressive symptoms severity (b = 0.11; 95% CI, 0.08 to 0.15). Age had statistically significant positive association with depression symptoms severity (b = 0.08; 95% CI, 0.02 to 0.14). Education level had a statistically significant negative association with depressive symptoms severity (b = −0.53; 95% CI, −0.97 to −0.09). Conclusions: Urban refugees experience high levels of both stigma and depression. Interventions aimed at reducing stigma could subsequently reduce depression among refugees living in urban areas.
Keywords: Depression; Stigma; Urban Refugees; Southwestern Uganda